Proteinuric and Non-proteinuric Diabetic Nephropathy: A Case of Siamese Twins? Reprinted for our readers interest from PJKD 2(8):37-43,2018 - Anwar, Muhammad Mubeen (Pakistan Journal of Kidney Diseases, 2021)
Diabetic nephropathy (DN) is the leading cause of chronic kidney disease (CKD) and its progression to end stage renal disease (ESRD) worldwide, necessitating renal replacement therapy (RRT) in the form of dialysis or transplant. Proteinuria had been the hall mark of diabetic nephropathy until recently, reduced glomerular filtration rate without proteinuria has been frequently observed and labelled as non-proteinuric diabetic nephropathy. The current review discusses the incidence and possible pathophysiology and associated issue with this entity.